APPLICATIONS OF NANOTECHNOLOGY IN WATER TREATMENT - Machado, Aline Belem; Rodrigues, Gabriela Zimmermann Prado; Feksa, Luciane Rosa; Berlese, Daiane Bolzan; Tundisi, José Galizia (Revista Conhecimento Online: Diversidade e Inclusão Social, 2019)
The industrial contamination, along with domestic effluents, agricultural and urban runoff are contaminating rivers and making it difficult for conventional water treatment to remove all the pollutants. This contamination can impact in the quality of rivers, in the quality of life of aquatic animals and can impact in the human health through the consumption of water. In order to improve the water quality, nanotechnology has been studied as an alternative to better remove contaminants, such as, heavy metals, oily water separation and antimicrobial activity. Besides, with the increase in industrialization along with the contamination of rivers, seawater could be an interesting alternative for drinking water source after adequate treatment. Nanomaterials are being studied as a possibility to remove salt from seawater, making it possible to drink. Howerver, there is a need to elucidate the potential risks to the environemt that these nanomaterials can cause. Therefore, the aim of this review is to describe some applications of nanotechnology in water treatment regarding metals, oil removal from water, antimicrobial activity and desalination in order to improve water quality, as well, as discuss their potential risk to the environment.